The Social Profiles of Occupational Therapy Students' Educational Groups - Tore Bonsaksen; Mari N. Eirum; Mary V. Donohue (Scholarworks @ WMU, 2015)
Background: Today's occupational therapy models emphasize that a person's choice of, satisfaction with, and performance in occupations are markedly influenced by the context. For students undergoing a group-based study module, the group is an important context factor. Until recently, there has been a lack of instruments available for the assessment of functioning and participation at the group level. This mixed methods pilot study aimed to examine occupational therapy students' perceptions of their group's level of functioning and course of development during one study module. Methods: The students' perceptions of their group's functioning were assessed in two ways: by examining their scores on the Social Profile (SP), a new instrument, and by examining their qualitative descriptions of the groups and how the groups developed over time. The sample consisted of four occupational therapy students. Results: Two students perceived their group functioning as stable over time. One student's scores indicated an increase in group functioning over time, whereas one student's showed a decrease. The interview statements showed varying degrees of connectedness with the SP items. Conclusions: Descriptions of stability and change corresponded very well with the students' SP trajectories, indicating content validity of the assessment as a whole.